Theoretical-conceptual background, methodical approaches and criteria for establishing business results in accounting and financial and economic thought of Galicia (second half of the XIX – first half of the XX century) - Lemishovska, O. (Видавництво Львівської політехніки, 2019)
The objective establishment of the level of efficiency (effectiveness) of the functioning of economic entities with the complexity of the architectonics of the economy becomes more problematic, and the system of criteria of efficiency becomes more complex and more debatable. In today's financial and accounting theories and, as a consequence, the practice of financial management, there are a number of debating questions about the system of performance indicators, methods of formalization. This actualizes multi-vector studies both in the accounting field and in the system of interdisciplinary research. The accounting methodology and the specific methodology for calculating performance indicators throughout the evolution of this science have always been based on one or the other financial doctrine. In the article are analyzed some aspects of contemporary financial doctrines and regulatory norms of different institutions that influenced the development of conceptual frameworks and methods of calculating performance indicators in accounting development of scientists of Galicia. The scientific validity of the approaches proposed in this article to improve the current basis of enterprise performance criteria is based on the justification of the use of historically formed ideas in the past in the designated territory and is based on the following postulates: accounting tools are the basic information system of any paradigm of financial results management; the process of forming a system of indicators of real and expected profits should be based on the principle of accounting – the assumption of continuity of the enterprise, which is also embodied in modern concepts of financial management of sustainable development. Using general scientific and interdisciplinary methods of cognition, historicalretrospective and historical-comparative methods, theoretical generalizations of basic principles of accounting practice were conducted and the content of Galicia's accounting opinion regarding the indicators of efficiency in relation to the provisions of the current financial and economic concepts was evaluated. The principles and content of reflecting the profitability of the enterprise in the writings of Western Ukrainian scientists are revealed and analyzed. On the basis of this historical and economic intelligence, an argument is made about the possibility of using some of the workings of Galician theorists in the field of finance and accounting to improve the modern system of performance indicators in accounting, financialanalytical and management theory and practice. In particular, it is proposed to take into account the provisions formulated at the time for evaluating the results of the enterprise based on changes in the capital due to economic factors, approaches to accounting for one-time (occasional) income or losses, and methods for the productive impact of the intangible component of capital on the evaluation of the enterprise efficiency. The proposed is in line with modern concepts of costoriented management, criteria for market-based tools for evaluating the effectiveness of companies.
Keywords: financial results; accounting; financial and economic doctrines; institutional environment; Galicia territory; conceptual and methodological developments of Western Ukrainian scientists; 657.412.7(477.8) «18/19»; 005.21